Future Directions in Reducing Gastrointestinal Disorders in Children With ASD Using Fecal Microbiota Transplantation - Żebrowska, Paulina; Łaczmańska, Izabela; Łaczmański, Łukasz (Frontiers in Cellular and Infection Microbiology, 2021)
Research on the use of fecal microbiota transplantation (FMT) in the treatment of disorders related to digestive system ailments in children with autism spectrum disorders (ASDs) is a new attempt in a therapeutic approach. There are very little scientific evidences available on this emerging alternative method. However, it appears to be interesting not only because of its primary outcome, relieving the gastrointestinal (GI) symptoms, but also secondary therapeutic effect of alleviating autistic behavioral symptoms. FMT seems to be also promising method in the treatment of another group of pediatric patients, children with inflammatory bowel disease (IBD). The aim of this study is to discuss the potential use of FMT and modified protocols (MTT, Microbiota Transfer Therapy) in the treatment of GI disorders in ASD children supported by reports on another disease, IBD concerning pediatric patients. Due to the few reports of the use of FMT in the treatment of children, these two patients groups were selected, although suffering from distant health conditions: neurodevelopmental disorder and gastrointestinal tract diseases, because of the the fact that they seem related in aspects of the presence of GI symptoms, disturbed intestinal microbiota, unexplained etiology of the condition and age range of patients. Although the outcomes for all are promising, this type of therapy is still an under-researched topic, studies in the group of pediatric patients are sparse, also there is a high risk of transmission of infectious and noninfectious elements during the procedure and no long-term effects on global health are known. For those reasons all obtained results should be taken with a great caution. However, in the context of future therapeutic directions for GI observed in neurodevelopmental disorders and neurodegenerative diseases, the topic seems worthy of attention.